Branding Activation as a Sustainable Image Building Process: Analysis of Events by Sejauh Mata Memandang - Ramadhani, Ayuningtias; Budiwaspada, Agung Eko (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Branding activation is part of the branding strategy in building and communicating the identity and values of a brand. This branding activation functions as a tool to interact directly with consumers through various activities such as events. Events are one of a series of branding activations because they have a direct connection with consumers, allowing for deeper and more personal interactions for brands to convey their image. In the context of sustainable branding, branding activation is a process that only aims to convey environmental, social, and economic values, but also to build deeper relationships with consumers by emphasizing the brand's commitment to sustainable practices. Through semiotic analysis, this research explores the role of branding activation in forming and communicating a sustainable brand image, with a focus on the